Tin in Human Bones - Jambor, Jaroslav; Smrcka, Václav (Anthropological Review, 1993)
The tin content in the bones of 149 skeletons from the 1st - 5th centuries A.D., and of 11 individuals of the recent population was determined. The bone samples were carbonized and analyzed through emission spectroscopy with a.c. excitation. The tin content in bones of recent populations not exposed to extra tin supply is about one order of magnitude higher than is the case with the bones od some populations that lived at the beginning of our era. The distribution of tin in long bones, dependent on age, as well as the sources and role of tin in environmental contamination are discussed.